Pyrolysis of Acacia nilotica bark: estimation of kinetic and thermodynamic parameters using model-free isoconversional methods - Singh A.K.; Parikh P.C.; Chakraborty J.P. (My University, 2025)
Pyrolysis of Acacia nilotica Bark (ANB) was investigated using KAS (Kissinger–Akahira–Sunose), FWO (Flynn-Wall-Ozawa), and Starink methods to study the kinetics and thermodynamics. Thermogravimetric analysis was carried out at four heating rate 5, 10, 20, and 30 °C/min in nitrogen atmosphere. DTG curves indicating weight-loss peaks move to higher temperatures at higher heating rates. More biochar was produced at higher heating rates as the rate of weight loss slowed down at higher heating rates. The average activation energy obtained by KAS, FWO, and Starink methods were 100.30, 107.59, and 100.22 kJ/mol, respectively. The pre-exponential factors ranged from 2.75*10-2 – 1.37*1015 for KAS, 1.11 – 1.20*1015 for FWO, and 3.27*10-2 – 1.44*1015 s−1 for Starink. Thermodynamic characteristics of ANB indicated that it contains potential energy for bioenergy generation and could produce higher yields of biochar. Criado's Z-master plots were constructed which depict that biomass degradation follows a multistep reaction mechanism. In the lower conversion range, it was observed that ANB decomposed using the (R2), (R3), and D2; and in the middle conversion range it followed (F2), (A4), (D4), and (D2) models and in the high conversion range it followed diffusion (R2) and (R3) model. © 2025 Elsevier Ltd